The Inventory of Complicated Spiritual Grief: Assessing Spiritual Crisis Following Loss - Burke, Laurie A. (Religions, 2016)
Following the death of a loved one, many grievers endorse spirituality as a source of both solace and strain. Studies show that some grievers struggle significantly with both their relationship with God and their faith community, a condition known as complicated spiritual grief (CSG). However, researchers have lacked a simple, multidimensional, well-validated, grief-specific measure of CSG. In this brief report, we reviewed the psychometric validation process and clinical utility of a measure called the Inventory of Complicated Spiritual Grief (ICSG), which was tested with 304 Christian grievers. The 18-item ICSG was shown to have strong internal consistency, high test-retest reliability, and convergent and incremental validity and supported a two-factor model, measuring one's insecurity with God and the disruption in one's religious practice.